From Modic 1 vertebral-endplate subchondral bone signal changes detected by MRI to the concept of 'active discopathy'. Issue 8 (14th May 2015) - Nguyen, Christelle; Poiraudeau, Serge; Rannou, François
Abstract : Late-1980s MRI-detected vertebral-endplate subchondral bone signal changes associated with degenerative disc disease as well as recent studies suggest that in some patients, non-specific chronic low back pain (NS cLBP) can be defined by specific clinical, radiological and biological features, for a concept of active discopathy. This concept allows for associating a particular NS cLBP phenotype to a specific anatomical lesion, namely those with Modic 1 signal changes seen on MRI. Local inflammation is thought to play a pivotal role in these changes. Other etiopathogenic processes may include local infection and mechanical or biochemical stress combined with predisposing genetic factors; treatment strategies remain debated. Modic 1 changes detected by MRI can be considered a first biomarker in NS cLBP. Such changes are of high clinical relevance because they are associated with a specific clinical phenotype and can be targeted by specific treatments.